The Purpose of Islamic Communication in Perspective of the Hadith (Sasaran Komunikasi Islam dalam Perspektif Hadis) - Setiawan, Daryanto; Helmi, Badrul; Muslim, Muslim (MODELING: Jurnal Program Studi PGMI, 2024)
Communication is one of the most fundamental activities in the life of mankind. Humans as social creatures must communicate with other humans. Because if humans do not communicate, these humans will gradually be isolated from their society, easily depressed, and will eventually die. So great are the benefits and functions of communication that many Westerners study and conduct research on communication, both intrapersonal communication, interpersonal communication, public communication and organizational communication. However, studies and research conducted by the Western world only focus on discussing human relationships, and very rarely do they examine communication with God, communication with subtle beings, and communication with Animals. In this study the author analyzes how the target of communication from the perspective of the Hadith of the Prophet. The method in this study uses the library method (library research) which is a data collection technique by conducting a study of books, journals, and other literature that has a relationship with related issues. The results of this study indicate that the Prophet's Hadith 1) Communicating with God, 2) Communicating with spirits, and 3) Communication with Animals, are relevant to several Western theories. Abstrak Komunikasi adalah salah satu aktivitas yang sangat fundamental dalam kehidupan umat manusia. Manusia sebagai makhluk sosial pasti melakukan komunikasi dengan manusia lainnya. Sebab jika manusia tidak melakukan komunikasi maka manusia tersebut lambat laun akan terisolasi dari masyarakatnya, mudah depresi, dan akhirnya akan meninggal dunia. Begitu besarnya manfaat dan fungsi dari komunikasi maka orang-orang Barat banyak yang mengkaji dan melakukan penelitian tentang komunikasi, baik komunikasi intrapersonal, komunikasi interpersonal, komunikasi publik maupun komunikasi organisasi. Akan tetapi kajian dan penelitian yang dilakukan dunia Barat hanya fokus membahas hubungan antarmanusia saja, dan sangat jarang sekali mereka meneliti tentang komunikasi dengan Tuhan, komunikasi dengan makhlus halus, dan komunikasi dengan Hewan. Dalam penelitian ini penulis menganalisis bagaimana sasaran komunikasi perspektif Hadis Nabi Saw. Metode dalam penelitian ini menggunakan metode pustaka (librery research) yakni teknik pengumpulan data dengan melakukan studi telaah pada buku, jurnal, serta literatur lain yang memiliki hubungan dengan masalah terkait. Hasil penelitian ini menujukan bahwa hadis Nabi 1) Berkomunikasi dengan Allah, 2) Berkomunikasi dengan makhluk halus, dan 3) Komunikasi dengan Hewan, relevan dengan beberapa teori dari Barat.